A critique on "An efficient numerical model for liquid water uptake in porous material and its parameter estimation". (1st February 2023) - Janssen, Hans
Abstract: In February 2019 this journal published the article "An efficient numerical model for liquid water uptake in porous material and its parameter estimation", (re)introducing the Scharfetter-Gummel numerical model for simulation of moisture transfer in building materials, and applying it for the inverse characterization of hygric properties based on a capillary absorption experiment. This critique voices concerns on the moisture transfer model defined and on the moisture transfer simulations performed. It moreover formulates doubts on the obtained identification and intended identifiability of the moisture transfer properties. This critique invites the article's authors to address these concerns, to confirm their outcomes' reliability.